Project Objectives - A Confused Concept - Baccarini, David (Bond University, 2011)
Project objectives are a core concept within the field of project management. This paper reports research findings that attempts to identify understandings of the term „project objectives”. Firstly, a review is undertaken of key project management literature pertaining to the concept of project objectives. Secondly, a survey is conducted of 37 members of the project management community. The research highlights a myriad of definitions of the term „project objectives”. The most common definition is that project objectives refers to the time and cost objectives of the project. However, there is some support for distinct alternative interpretations, namely that project objectives refers to the deliverables of the project, or to the project's benefits. It is concluded that the project team needs to have a consistent understanding of project objectives to avoid miscommunication. Alternatively, the term „project objectives‟ should be avoided and less ambiguous terms used, such as deliverables, benefits and time and cost objectives